1985
DOI: 10.1093/ajcp/83.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-Cell Lymphoma: Aggressive Disease with Heterogeneous Immunotypes

Abstract: Eleven patients with mature or peripheral T-cell lymphoma (PTL), other than mycosis fungoides, were identified using an extensive battery of T- and B-cell markers. Eight cases had a histologic diagnosis of either diffuse large cell or mixed lymphoma, three of small cell type. All cases had one or more "mature" T-antigens and an absence of B- and immature T-antigens. Assessment of T-antigens included E-rosettes (Er), anti-Leu 1-7 and Tdt. The authors delineated striking heterogeneity of T-antigen expression: 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1
2

Year Published

1985
1985
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(35 citation statements)
references
References 21 publications
5
27
1
2
Order By: Relevance
“…Most prior studies have explored the importance of determining the B-cell versus T-cell groups or the presence versus absence of surface immunoglobulins (3)(4)(5)(6)(7)(8). More recent trials have explored additional surface and nuclear antigens using newer monoclonal antibodies with some success including the activation factors, transferrin receptor (17), and HLA-DR (15,16), and proliferation antigens such as (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most prior studies have explored the importance of determining the B-cell versus T-cell groups or the presence versus absence of surface immunoglobulins (3)(4)(5)(6)(7)(8). More recent trials have explored additional surface and nuclear antigens using newer monoclonal antibodies with some success including the activation factors, transferrin receptor (17), and HLA-DR (15,16), and proliferation antigens such as (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to more accurately predict outcome prior to treatment for patients with DLCL, investigators have explored the potential prognostic value of determining the immune phenotype of these NHLs. The results of those efforts are inconclusive with some studies showing no prognostic value (3)(4)(5) and others suggesting utility for determining the immune phenotype of DLCL (6)(7)(8). These disparate results may be related to any of several problems of past study designs including; small numbers of patients studied, comparisons between heterogenous histologic subgroups, and selection of monoclonal antibodies having little biological significance.…”
Section: Introductionmentioning
confidence: 99%
“…In regard to the latter, lymphoblastic lymphoma and mycosis fungoides are well-described entities. Recently, several investigators have reported the clinicopathologic features of peripheral T-cell lymphomas [2][3][4][5][6][7]. In general, patients are usually in their fifth to seventh decade of life, have B symptoms, and advanced stages (III of IV) of dis ease [2][3][4][5][6][7].…”
Section: Om M Entmentioning
confidence: 99%
“…Recently, several investigators have reported the clinicopathologic features of peripheral T-cell lymphomas [2][3][4][5][6][7]. In general, patients are usually in their fifth to seventh decade of life, have B symptoms, and advanced stages (III of IV) of dis ease [2][3][4][5][6][7]. Histologically, such lymphomas are mainly in termediate-or high-grade, according to the Working For mulation Classification [8], Moreover, these lymphomas have a propensity for extranodal involvement, primarily of the skin, bone marrow, and lungs [2][3][4][5][6][7].…”
Section: Om M Entmentioning
confidence: 99%
See 1 more Smart Citation